New Woman in Early Twentieth-Century Chinese Fiction - Feng, Jin (Purdue University Press, 2004)
Jin Feng proposes that representation of the "new woman" in Communist Chinese fiction of the earlier twentieth century was paradoxically one of the ways in which male writers of the era explored, negotiated, and laid claim to their own emerging identity as "modern" intellectuals.